POTENSI PENGGUNAAN BEBERAPA VARIETAS SORGUM MANIS (Sorghum bicolor (L.) Moench) SEBAGAI TANAMAN PAKAN - Mustikoweni Purnomohadi (The East Java Biological Society, 2006)
Sweet sorghum is a versatile crop that can be used as grain crop, sugar alcohol production and even as forage crop. The aim of this study was to evaluate the potential use of sweet sorghum either as grain crop or forage crop. The experiment used four varieties of sweet sorghum: Rio, Cawley, Keller and Wray, which were planted in polybag with six replication using Completely Randomized Design. The result of the research showed that Keller and Wray had longer vegetative growth, and good quality of chemical composition for forage than Rio and Cawley.